Introduction: community service learning and the South African research agenda - Erasmus, Mabel (University of the Free State, 2005)
The integration of research and community service learning (also referred to as service learning or service-learning in this volume) opens up opportunities for contributing to the much discussed transformation of higher education in South Africa, through which institutions of higher education are urged to become more democratic, more responsive to community challenges, and conducive to partnership-building with a wide variety of stakeholders. The twofold premise of this introductory article is the following: service learning as a pedagogy is strengthened through scholarly inquiry and, secondly, the South African research agenda can be advanced through the philosophy and epistemology of service learning that promotes collaborative, open systems of knowledge production. The aim of the article is to establish why and how the above should and could be achieved, placing the other contributions to this issue of Acta Academica Supplementum within the framework of a more inclusive service learning research agenda for South Africa.

Die integrasie van navorsing en samelewings- of gemeenskapsdiensleer (ook bloot diens- leer genoem in hierdie bundel) skep geleenthede om by te dra tot die veelbesproke transformasie van hoër onderwys in Suid-Afrika, waardeur hoëronderwysinstellings aangespoor word om meer demokraties te wees, beter te respondeer op die uitdagings van gemeenskappe, en om die bou van vennootskappe met ’n wye verskeidenheid be- langhebbendes te bevorder. Die tweeledige aanname van hierdie inleidende artikel is die volgende: diensleer as ’n pedagogiese metode word versterk deur vakkundige ondersoek en, tweedens, die Suid-Afrikaanse navorsingsagenda kan bevorder word deur die filosofie en epistemologie van diensleer wat samewerkende, oop sisteme van kennisproduksie bevorder. Die doel van die artikel is om te bepaal waarmee en hoe bogenoemde bereik kan word, en om die ander bydraes in hierdie uitgawe van Acta Academica Supplementum binne die raamwerk van ’n meer inklusiewe navorsingsagenda vir diensleer in Suid- Afrika te plaas.
Keywords: South Africa; Research; Community service learning; Higher education; Transformation